DO FLAGGING LETTERS FROM HOSPITAL PALLIATIVE CARE TEAMS IMPROVE COMMUNITY CARE OF PATIENTS APPROACHING END OF LIFE?. Issue Volume 5: Issue (2015)Supplement 1 (1st March 2015) - Georgiade, K; Kelt, S; McKenna, E; Hookey, C
Abstract : Introduction: The Gold Standards Framework (GSF) was developed to improve primary palliative care and has now extended to all health care settings. The palliative care team at Royal Stoke University Hospital developed a system to alert patients' GPs, by means of a "flagging letter", that the patient has an anticipated prognosis less than 12 months and would benefit from entry onto the practice GSF register. The letter suggests consideration of discussions about resuscitation status and end of life care preferences. Aim(s) and method(s): To assess the effect of these letters on patient care including enrolment onto GSF, advance care planning, and DNAR discussions. Retrospective data analysis over 2 month period with focus on distinguishing any differences between those enrolled or not enrolled onto GSF. Results: A large proportion of patients were enrolled on practice GSF registers (68%). 86.44% had DNAR orders irrespective of their enrolment to GSF.Patients on GSF registers were more likely to have district nurses involvement and anticipatory medication in place (38% compared to 6%). In 77% of all patients preferred place of death was documented (of whom 71% were registered to GSF) and this was achieved in 73% of cases. Conclusion(s): Highlighted need for open discussions regarding advance directives and better documentation of preferred place of death. Overall though, identification of patients with limited prognosis and the communication of this information to primary care can lead to improvements in care for end of life patients.